2007
DOI: 10.1021/ie0704492
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Performance of Polymerizable Room-Temperature Ionic Liquids as Gas Separation Membranes

Abstract: Room-temperature ionic liquids (RTILs) with polymerizable groups can be readily converted into solid, dense poly(RTILs) for use as gas separation membranes. A series of RTIL monomers with varying length n-alkyl substituents were synthesized and converted into polymer films. These membranes were tested for their performance in separations involving CO 2 , N 2 , and CH 4 . CO 2 permeability was observed to increase in a nonlinear fashion as the n-alkyl substituent was lengthened. CO 2 /N 2 separation performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
422
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(433 citation statements)
references
References 49 publications
9
422
1
Order By: Relevance
“…The diffusion coefficient through the membranes is calculated from the transition regime of mass transfer through a dense material [41]:…”
Section: Characterizationmentioning
confidence: 99%
“…The diffusion coefficient through the membranes is calculated from the transition regime of mass transfer through a dense material [41]:…”
Section: Characterizationmentioning
confidence: 99%
“…8,9 These RTILs are more stable but they require particular polymerizable groups and sophisticated membrane preparation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…24 The potential of such ILs in gas separations has been recently reported with polymer gas separation membranes based on polymerizable etherderivatized ILs. 25 No thermodynamic property of cyanoalkyl-substituted ILs was found in the literature. Zhao and co-workers showed that these functionalized ILs should be used as electrolytes for lithium secondary batteries.…”
Section: Introductionmentioning
confidence: 99%